(untitled) (Estudios humanísticos. Geografía, historia y arte, 1998)
The following paper studies a document of don Juan’s Chancery. Infante don Juan ( 1262- 1 3 19), son of the king Alphonse the Tenth of Castilla and León, appears in this document as the León, Galicia and Seville king.